Performance profiling: A role for sport science in the fight against doping? - Schumacher, Y. O.; Pottgiesser, T. (International Journal of Sports Physiology and Performance, 2009)
In recent years, antidoping strategies underwent a significant development, from purely biochemical analyses and the detection of substances in urine samples to a biological approach, using blood samples, longitudinal monitoring, and probabilistic techniques. Nowadays, the appropriate timing of testing and the targeting of the athletes to be tested with antidoping tests is a major issue. A new strategy to improve the targeting of suspicious athletes might be the longitudinal monitoring of individual performances. By these means, suspect athletes might be identified, as doping will not only alter their blood or steroid profiles, but ultimately boost their performance, as well. Through the proposed approach, the effectiveness in the fight against doping might be improved considerably.